MENINGKATKAN KEMAMPUAN MENGENAL LAMBANG BILANGAN MELALUI KEGIATAN BERMAIN ANGKA BERGAMBAR - Nur Alim Amri; Ilmia Amalia; Marup Marup (Jurnal Panrita, 2022)
This study aims to find out how to improve the ability to recognize number symbols through the activity of playing with illustrated numbers in children in the B3 Tk Aisyiyah Bustanul Athfal group, Mamajang District, Makassar City. The theoretical study in this research is the ability to recognize number symbols is a form of a child's ability to recognize and recognize numbers that represent many objects. Playing is an activity that is carried out spontaneously and is very fun for children, illustrated numbers are media that contain pictures and number symbols made of used paper and cardboard and can help educators to be able to develop children's basic knowledge, especially symbols of numbers or numbers, so that children are mentally ready to take part in further mathematics lessons such as the introduction of number symbols, colors, shapes and sizes, and cognitive development is an arrangement that will describe a person's mental abilities which include the ability to solve problems, think abstractly and learn from experience. This type of research is classroom action research which consists of two cycles where each meeting is held three times. Research procedures include planning, implementation, observation, and reflection. The subjects in this study were 33 children of B3 group of TK Aisyiyah Bustanul Athfal. In cycle I, with a percentage of 34.98%, it is categorized as Starting to Develop (MB), while in cycle II, with a percentage of 83.24%, it is categorized as Very Well Developed (BSB). With this the results of the study indicate that there is an increase in the ability to recognize number symbols in children in the B3 group of TK Aisyiyah Bustanul Athfal, Mamajang District, Makassar City through the activity of playing with picture numbers.